Low Vitamin D Status Is Associated With Impaired Bone Quality and Increased Risk of Fracture‐Related Hospitalization in Older Australian Women. (1st August 2019) - Zhu, Kun; Lewis, Joshua R; Sim, Marc; Prince, Richard L
ABSTRACT: The vitamin D debate relates in part to ideal public health population levels of circulating 25‐hydroxyvitamin D (25OHD) to maintain bone structure and reduce fracture. In a secondary analysis of 1348 women aged 70 to 85 years at baseline (1998) from the Perth Longitudinal Study of Aging in Women (a 5‐year calcium supplementation trial followed by two 5‐year extensions), we examined the dose‐response relations of baseline plasma 25OHD with hip DXA BMD at year 1, lumbar spine BMD, and trabecular bone score (TBS) at year 5, and fracture‐related hospitalizations over 14.5 years obtained by health record linkage. Mean baseline plasma 25OHD was 66.9 ± 28.2 nmol/L and 28.5%, 36.4%, and 35.1% of women had levels <50, 50 to 74.9, and ≥75 nmol/L, respectively. Generalized additive models showed that total hip and femoral neck BMD and TBS, but not spine BMD, were higher with increasing plasma 25OHD up to 100 nmol/L. Compared with those with 25OHD <50 nmol/L, women with 25OHD ≥75 nmol/L had significantly higher total hip and femoral neck BMD at year 1 (3.3% to 3.9%) and TBS at year 5 (2.0%), all P < 0.05. During the follow‐up, 27.6% of women experienced any fracture‐related hospitalization and 10.6% hip fracture‐related hospitalization. Penalized spline regression models showed a decrease in risk with increased 25OHD levels up to 65 nmol/L and 75 nmol/L for hip fracture and any fracture‐related hospitalization, respectively. Cox regression grouped analyses showed that compared with women with 25OHD <50 nmol/L, those with 25OHD levels 50 to 74.9 and ≥75 nmol/L had significantly lower risk for hip fracture [HR 0.60 (95% CI, 0.40 to 0.91) and 0.61 (95% CI, 0.40 to 0.92), respectively], and any fracture‐related hospitalization [HR 0.77 (95% CI, 0.59 to 0.99) and 0.70 (95% CI, 0.54 to 0.91), respectively]. In older white women, 25OHD levels >50 nmol/L are a minimum public health target and 25OHD levels beyond 75 nmol/L may not have additional benefit to reduce fracture risk. © 2019 American Society for Bone and Mineral Research.